Innovations in Tuberculosis Management: Advancements in Drug-Resistant TB Treatment and Rapid Diagnostics - Shireen Siddique1; Priyanka Sharma (International Journal of Antibiotics, 2025)
Tuberculosis (TB) remains one of the deadliest infectious diseases worldwide, exacerbated by the increasing prevalence of drug-resistant strains, such as multidrug-resistant (MDR-TB) and extensively drug-resistant TB (XDR-TB). Despite advancements in first-line and second-line treatments, resistance to conventional antibiotics has complicated therapeutic strategies, necessitating novel approaches. This mini review explores emerging advancements in TB treatment, including gene editing technologies, such as CRISPR, which offer potential for precise targeting of drug-resistant bacterial strains. Additionally, recent research has uncovered mechanisms underlying bedaquiline’s enhanced efficacy in MDR-TB treatment, revealing metabolic vulnerabilities in resistant strains. Rapid diagnostic tools, including CRISPR-based platforms, have significantly improved TB detection and drug resistance profiling, enabling early and accurate interventions. Moreover, the development of shorter, all-oral regimens, such as the WHO-recommended BPaLM and BPaL regimens, has demonstrated high treatment success rates while reducing toxicity and improving patient adherence. These advancements signify a transformative shift in TB management, paving the way for more effective, patient-friendly, and sustainable treatment strategies.
Keywords: CRISPR technology; Tuberculosis; bedaquiline; drug-resistant TB; rapid diagnostics